2007
DOI: 10.1088/0953-4075/41/1/015401
|View full text |Cite
|
Sign up to set email alerts
|

Optical switching in nonlinear photonic crystals lightly doped with nanostructures

Abstract: A possible switching mechanism has been investigated for nonlinear photonic crystals doped with an ensemble of non-interacting three-level nanoparticles. In this scheme, an intense pump laser field is used to change the refractive index of the nonlinear photonic crystal while a weaker probe field monitors an absorption transition in the nanoparticles. In the absence of the strong laser field the system transmits the probe field when the resonance energy of the nanoparticles lies near the edge of the photonic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…27 Beyond the more widely discussed methods, a number of other concepts repeatedly resurface in the primary literature. These include, for example, systems based on photonic crystals with cross-waveguide geometries, offering switching action through the optical Kerr effect; [28][29][30] surfaceplasmon polariton media, in which light-induced dielectric modification at an interface affects the transmission of throughput radiation; [31][32][33] azobenzene-containing materials, which have differing optical properties for the trans and cis configurations, reversibly interchangeable by photoisomerization, [34][35][36] and various schemes based on films of bacteriorhodopsin, a light-harvesting protein with unique nonlinear optical properties. [37][38][39][40][41] The present paper reports an in-depth analysis of a very different all-optical switching mechanism-initially outlined by one of the present authors [42][43][44] -based on the optical con-trol of resonance energy transfer ͑RET͒ between molecules.…”
Section: Introductionmentioning
confidence: 99%
“…27 Beyond the more widely discussed methods, a number of other concepts repeatedly resurface in the primary literature. These include, for example, systems based on photonic crystals with cross-waveguide geometries, offering switching action through the optical Kerr effect; [28][29][30] surfaceplasmon polariton media, in which light-induced dielectric modification at an interface affects the transmission of throughput radiation; [31][32][33] azobenzene-containing materials, which have differing optical properties for the trans and cis configurations, reversibly interchangeable by photoisomerization, [34][35][36] and various schemes based on films of bacteriorhodopsin, a light-harvesting protein with unique nonlinear optical properties. [37][38][39][40][41] The present paper reports an in-depth analysis of a very different all-optical switching mechanism-initially outlined by one of the present authors [42][43][44] -based on the optical con-trol of resonance energy transfer ͑RET͒ between molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, highly nonlinear polymer and nanocomposite polymer materials have outperformed semiconductor materials in terms of large Kerr coefficient and ultrafast response speed [3,4,7] . Although the fabrication methods for high-quality threedimensional (3D) polymeric PCs have greatly improved in the recent years [8,9] , the appropriate technique for fabricating polymeric NPC slab structures remains at its initial stages.…”
mentioning
confidence: 99%
“…[12][13][14] It has been found that the number of bound states within the waveguides depended on the width and well depth and the Hetero-structure have been used to develop devices such as resonant cavities 15 , waveguides 16 and filters 17 . Meanwhile nonlinear nanophotonic coupling waveguides induced by laser or stress field have also been investigated both theoretically [18][19][20] and experimentally [21][22] . Nonlinear photonic waveguides are formed by embedding Kerr-nonlinear photonic crystals in a linear photonic crystal.…”
Section: Introductionmentioning
confidence: 99%